Electrical effects in superfluid helium. I. Thermoelectric effect in einstein's capacitor - Ledenyov, D.O.; Ledenyov, V.O.; Ledenyov, O.P. (Вопросы атомной науки и техники, 2014)
The Einstein's ideas about the thermodynamical fluctuational nature of some electrical phenomena and the difference of electrical potentials U in a capacitor at temperature T were proposed in 1906-1907. On base of these ideas we explain the experimental results, which were recently observed under the action of the second sound standing wave in the electrical capacitors which take placed in the superfluid 4 He and in the torsional mechanical resonator. The Einstein's approach, based on the interrelation of thermal, mechanical and electrical fluctuations, allows to obtain the quantitative results, coinciding with the experimental datas for the correlations of the alternate low temperatures difference in second sound wave and alternate electric potentials difference between the capacitor plates in superfluid helium at as well as in the rotating mechanical oscillator.